Evaluation of Immunohistochemistry Technique in Detecting HER2 Overexpression in Invasive Ductal Breast Carcinoma Using Fluorescence in-situ Hybridization Method - Azar Baradaran; Parvaneh Hajalikhani; Mohammad Kazem Gheybi; Mohammad Reza Mohajeri; Ali Mehrabi-Koushki (مجله دانشکده پزشکی اصفهان, 2016)
Background: Breast cancer is the most common cancer among women. HER2 gene is a proto-oncogene that encodes the receptor of tyrosine kinase from epidermal growth factor receptor (EFGR) family. It is an important prognostic factor with a determinant role in treatment of breast cancer. There is no globally accepted method for determining the status of this gene and the method of choice is still a matter of debate. We aimed to evaluate the validity of immunohistochemistry (IHC) method in predicting HER2 status using fluorescence in-situ hybridization (FISH) method and also, to investigate some clinicopathological variables associated with HER2 amplification.